Cytology smears as excellent starting material for next‐generation sequencing‐based molecular testing of patients with adenocarcinoma of the lung. Issue 1 (16th September 2016) - Velizheva, Nadezda P.; Rechsteiner, Markus P.; Wong, Christine E.; Zhong, Qing; Rössle, Matthias; Bode, Beata; Moch, Holger; Soltermann, Alex; Wild, Peter J.; Tischler, Verena
Abstract : BACKGROUND: Molecular testing of lung adenocarcinomas (ADCs) is crucial for therapy stratification of patients. Because of the often limited diagnostic material, the authors aimed to explore the suitability of cytology smears for next‐generation sequencing (NGS) and compared the results with concurrent histological specimens or cell blocks. METHODS: A total of 16 formalin‐fixed paraffin‐embedded (FFPE) ADCs with known genetic alterations were used as the first cohort for targeted DNA and RNA sequencing. In the second cohort of 8 cases, 8 cytological smears were compared with matching histological specimens or cell blocks for the study. For NGS library amplification, commercially available panels for DNA and RNA sequencing were applied. The Ion Torrent Personal Genome Machine and the Ion Reporter workflow (version 5.0) were used for sequencing. RESULTS: All DNA libraries derived from FFPE and non‐formalin‐fixed cytological smear samples produced acceptable quality metrics, thereby enabling successful targeted DNA sequencing (100% performance). Targeted RNA sequencing failed in 1 FFPE case and 1 cytology probe by not reaching enough mapped fusion reads (92% performance rate). All previously detected mutations and gene rearrangements could be confirmed (sensitivity of 100%), whereas specificity of the DNA‐based NGS assay reached 96%. CONCLUSIONS: The results of the current study demonstrated the suitability of non‐formalin cytology specimens for the simultaneous NGS testing of lung ADCs using amplicon resequencing panels. These assays allowed for the input of cytological smears equal to concurrent histology or cell blocks and proved to be accurate in the detection of therapeutically actionable somatic mutations and gene rearrangements. Cancer Cytopathol 2017;125:30‐40 . © 2016 American Cancer Society . Abstract : Cytology smears have proven to be an excellent substrate for next‐generation sequencing‐based amplicon resequencing of lung adenocarcinomas. This application note enables the identification of predictive biomarkers, even in samples that were previously regarded as "wild‐type" cases and as not having enough tumor cell content for standard molecular testing